Factors related to self-medication in the student population of nursing and midwifery at the Private University of Huancayo. - Andamayo Flores, Diana Esmeralda (2020)
Self-medication can be deﬁned generically as the administration by choice, or by unqualiﬁed advice, medicines to relieve symptoms or cure a disease. Self-medication is a problem more complex since entering the population attributable aspects such as medical education, culture, habits and customs that are somehow inﬂuenced by the big marketing machine that have drug manufacturing companies. The investigation considered to determine the factors related to self-medication in the student population of nursing and midwifery at the Private University of Huancayo. The design that was used corresponds to the objectives of an investigation by reference to the nature of the variable (cause - effect) used in the formulation of the problem. According to the results of self-medication is said to exist in the student population, still nursing career for a 96.83% and 94.12% in obstetrics. The drugs most are self- medicate antibiotics, analgesics and anti- inﬂammatory in percentages of 69.04% in students studying nursing and 66.18% in obstetrics, pathological processes by which self-medicate are common cold and body aches 47.62% in nursing students and 51.47% in obstetrics. The media that inﬂuenced the students of the Nursing Careers for self-medication were: TV 64.28% and for students of obstetrics by 60.29%.